1997
DOI: 10.1038/sj.onc.1201437
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human N8 protein

Abstract: We have shown before that the N8 mRNA is expressed at higher levels in lung tumor and lung tumor-derived cell lines than normal lung cells. In this paper, we have characterized the N8 protein, and studied its properties. The N8 gene encodes a major 24 kDa protein and its expression correlates well with the N8 mRNA expression pattern observed in dierent cell lines. N8 protein is capable of forming a homodimer or multimeter in vitro. It is a phosphorylated cytoplasmic protein and phosphorylation occurs mainly at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…A potential cytoskeletal role for CRHSP-28 in epithelial cell function was described previously based on the finding that its expression is induced dramatically after activation of an epithelial gene program in mesenchymal cells by the adenoviral E1a protein (23). The E1a protein induces the expression of a number of epithelial specific cytoskeletal regulatory proteins including desmoplakin, desmogelin, desmocolin, E-cadherin, and the cytokeritins K8/K18 (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential cytoskeletal role for CRHSP-28 in epithelial cell function was described previously based on the finding that its expression is induced dramatically after activation of an epithelial gene program in mesenchymal cells by the adenoviral E1a protein (23). The E1a protein induces the expression of a number of epithelial specific cytoskeletal regulatory proteins including desmoplakin, desmogelin, desmocolin, E-cadherin, and the cytokeritins K8/K18 (40).…”
Section: Discussionmentioning
confidence: 99%
“…Also known as D52 (21), N8 (22,23), R10 (24), and CSPP-28 (25), this protein has been identified based on its overexpression in transformed epithelial cells (21,22,24) and Ca 2ϩ -sensitive phosphorylation in gastric mucosa (25). Moreover, Byrne et al (26) demonstrated that CRHSP-28 belongs to a novel tumor protein D52 family (TPD52) comprised of at least three homologous genes that may undergo alternative splicing to create different protein products (27).…”
mentioning
confidence: 99%
“…38,39 Enzymes such as lactate dehydrogenase, 40 protein disul®de isomerase (thyroid hormone binding protein) 41 ± 43 and catechol Omethyltransferase 44 ± 46 have also been shown to be overexpressed in a variety of tumor tissues. The gene that encodes N8L (D52 homolog, a leucine zipper protein) 47,48 is located at chromosome 8q21, a region that is frequently ampli®ed in breast cancer cells. 49 Pini et al 53 performed phage antibody selection on a recombinant protein, ED-B of ®bronectin, eluted from a 2D gel.…”
Section: Discussionmentioning
confidence: 99%
“…PrLZ is expressed specifically in human prostate in an androgen-responsive manner, mainly in the epithelial compartment. The COOH-terminal region of PrLZ is identical to tumor protein D52 (TPD52), which has been isolated due to its abnormally elevated expression in breast cancer (3) and lung cancer (4). In the NH 2 -terminal region, however, PrLZ extends with a unique sequence of 46 amino acid residues.…”
mentioning
confidence: 99%